William James and the Modernist Esthetics of Religion. Issue 1 (7th March 2014) - Porterfield, Amanda
<x content-type="archive" xml:space="preserve">Abstract</x> In his intellectual biography, William James: In the Maelstrom of American Modernism, Robert Richardson never defines modernism, and never addresses the reasons for its turbulence in America. But he does present the maelstrom through his subject, showing how James helped drive the modernist sensibility he inhabited—a whirlwind of creativity and intellectual passion "whose leading ideas, " to quote Richardson, "are still so fresh and challenging that they are not yet fully assimilated by the modern world they helped to bring about." Presenting James as an intellectual activity, Richardson focuses on bringing the emotional background of that activity into view, chronicling James's intellectual history as splashes from a turbulent stream of consciousness. The book's dedication to Annie Dillard next to the book's epigraph from James reveals Richardson's respect for the volatility both writers represented. The dedication is: "For Annie, who wrote, 'we have less time than we knew and that time buoyant, and cloven, lucent, missile, and wild, '" followed by the epigraph from James testifying that, "[life] feels like a real fight—as if there were something really wild in the universe which we, with all our idealities and faithfulnesses, are needed to redeem."